2017
DOI: 10.1071/rd15514
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin-like growth factor 1 on cross-bred Bos indicus cattle germinal vesicle oocytes exposed to heat shock

Abstract: Germinal vesicle (GV) oocytes are susceptible to heat stress. However, neither the cellular mechanisms triggered by elevated temperature nor the thermoprotective effects of insulin-like growth factor (IGF) on GV oocytes are completely understood. Therefore, a series of experiments was conducted to determine the direct effects of IGF1 (0, 12.5, 25, 50 and 100ng mL) on heat-treated GV oocytes. Butyrolactone-arrested GV oocytes were cultured at 38.5°C (control) or 41°C (heat shock; HS) for 14h in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Alterations in cortisol serum concentrations were very clear after acute stressful situations, like Nellore management on corral (Lima et al 2017 ) and after weaning (Chaves et al 2015 ). Black Angus heifers assigned to pen with four different shade treatments for 8 weeks during summer showed different serum cortisol concentration in accord with shade treatment (Brown-Brandl 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in cortisol serum concentrations were very clear after acute stressful situations, like Nellore management on corral (Lima et al 2017 ) and after weaning (Chaves et al 2015 ). Black Angus heifers assigned to pen with four different shade treatments for 8 weeks during summer showed different serum cortisol concentration in accord with shade treatment (Brown-Brandl 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the above, we can see that the type II receptor (BMPRII) has great importance for the adequate follicular development and acquisition of oocyte competence, besides being a common receptor for GDF9 and BMP15, it is still responsible for initiating a signaling cascade that comprises several events, starting from the phosphorylation and activation of the type I receptors. BMPRII, or receptor of bone morphogenetic protein type II, is expressed in the granulosa cells in the early stages of folliculogenesis in both ruminant primordial follicles as in preantral follicles in rodents, and continues to be expressed in all subsequent stages of follicular development ( Juengel and McNatty, 2005 ; Lima, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that zebu breeds are more tolerant to heat ( Hansen, 2004 ). However, there is a limit to this, as heat stress at different temperatures and durations during the IVM of zebu COCs impairs in vitro embryo development ( Lima et al., 2017 ; reviewed by Paula-Lopes et al., 2013 ). However, to the best of our knowledge, no study has demonstrated the effects of low-temperature stress during the IVM of bovine oocytes.…”
Section: Discussionmentioning
confidence: 99%